EXPLORING ANIMAKER AS A MEDIUM OF WRITING A DESCRIPTIVE TEXT: EFL STUDENTS’ CHALLENGES AND PROMOTED ASPECTS OF DIGITAL STORYTELLING LITERACY - Tiarma Marpaung; Erny Selfina Nggala Hambandima (Academic Journal of Educational Sciences, 2019)
Animaker, as one of the digital storytelling tools to write a descriptive text in the learning intervention, is promoted in this pilot study. As a part of a classroom action research, this study is conducted to build the students’ digital storytelling literacy. Firstly, it aims at investigating the students’ challenges of using Animaker as a medium to write a descriptive text. Secondly, it is to describe how the aspects of digital storytelling were promoted by Animaker. A descriptive qualitative method is used to analyze the data gained from a questionnaire and the document of students’ animated videos created by using Animaker. The results found that the process of inserting audio files was the most difficult to do for 80% of the students. Around 20%-40% of them were also challenged by the way of adjusting the duration and the volume of the audio inserted on each page. The use of Animaker also promoted the students’ diverged digital storytelling literacy in 11 aspects; the topic, purpose, creator, audience, organization, narration, multimedia, educational value, mechanics, sources, and originality. Then, it is suggested that the use of Animaker should apply certain strategies to minimize the challenges and to increase the students’ digital storytelling literacy. Finally, the researchers recommend this tool to be used frequently in EFL learning as a tool to reinforce the students’ digital storytelling literacy.